Intraoperative Protective Mechanical Ventilation in Dogs: A Randomized Clinical Trial - Rodrigues, Renata R.; Ambrósio, Aline M.; Engbruch, Aline M.; Gonçalves, Lucas A.; Villela, Paula A.; Sanchez, Ana F.; Fantoni, Denise T. (Frontiers in Veterinary Science, 2022)
Objective: To evaluate gas exchange, respiratory mechanics, and hemodynamic impact of mechanical ventilation with low tidal volume (VT) in dogs with the use of positive end-expiratory pressure (PEEP) or preceded by alveolar recruitment maneuver (ARM). Study design: Prospective randomized clinical trial. Animals: Twenty-one healthy client-owned mesocephalic healthy dogs, 1-7 years old, weighing 10-20 kg, and body condition scores 4-6/9 admitted for periodontal treatment. Methods: Isoflurane-anaesthetized dogs in dorsal recumbency were ventilated until one hour with a volume-controlled ventilation mode using 8 mL kg-1 of VT. The dogs were distributed in 2 groups: in the ARM group, PEEP starts in 0 cmH2O, increasing gradually 5 cmH2O every 3 minutes, until reach 15 cmH2O and decreasing in the same steps until 5 cmH2O, maintaining this value until the end; and PEEP group, in which the pressure 5 cmH2O was instituted from the beginning of anesthesia and maintained the same level up to the end of the anesthesia. Cardiopulmonary, metabolic, oxygenation parameters, and respiratory mechanics were recorded after the anesthesia induction (baseline - BL), 15, 45, and 75 minutes after BL and during the recovery. Results: The ARM increased the static compliance (Cst) (15 minutes after baseline) when compared with baseline moment (24.9 ± 5.8 mL cmH20-1 versus 20.7 ± 5.4 mL cmH20-1 – p = 0.0364), oxygenation index (PaO2/FIO2) (505.6 ± 59.2 mmHg versus 461.2 ± 41.0 mmHg – p = 0.0453) and reduced the shunt fraction (3.4 ± 2.4% versus 5.5 ± 1.6% - p = 0.062). In the PEEP group, no statistical differences were observed concerning the variables evaluated. At the beginning of the evaluation, the driving pressure (DP) before ARM was significantly greater than all other evaluation time points (6.9 ± 1.8 cmH20). Conclusions and clinical relevance: The use of 8 mL kg-1 of VT and 5 cmH20 PEEP without ARM maintain adequate oxygenation and mechanical ventilation in dental surgeries for up to one hour. The use of ARM slightly improved compliance and oxygenation during the maneuver.